The extent and uptake of mathematics support in higher education: results from the 2018 survey. (30th September 2019) - Grove, Michael; Croft, Tony; Lawson, Duncan
Abstract: In response to the well-documented challenges associated with the 'mathematics problem' in UK higher education, many institutions have implemented a programme of mathematics support. Previous surveys within the UK, undertaken in 2001, 2004 and, most recently, 2012, have shown growth in the number of institutions offering such support and indicate that the dominant form of provision is through a drop-in model. Here we report on a 2018 survey of higher education providers in England and Wales undertaken to establish not only the extent of current provision but also understand the scale of its delivery. We find that overall the proportion of higher education institutions offering mathematics support remains broadly the same, but there is considerable variation in how this support is delivered within institutions. While the drop-in model remains most common, we see evidence that the methods used to provide mathematics support are expanding and that the range of levels and subjects studied of targeted student cohorts is widening. For the first time we are able to report on the volume of use of mathematics support by students across England and Wales, and although dependent upon the institutional context, we see clear evidence of the extensive use being made of it by learners.